Tilapia hatchery production in Nigeria: Manual for best biosecurity practices - Mohamed Din, Mohamed Shariff; Subasinghe, Rohana (WorldFish, 2024)
The aim of these collective pioneering efforts is to establish a resilient and biosecure environment for farming tilapia in Nigeria. In doing so, they combine national goals of food security, economic prosperity and sustainable aquaculture practices. The manual provides crucial guidelines and protocols for ensuring the health and biosecurity of tilapia hatchery operations. We hope it will prove instrumental in guiding fish farmers across Nigeria to protect their stocks from diseases. This, in turn, will enhance yields and ensure the long-term success of their aquaculture endeavors.